The Effect Of Students’ Diary On Students’ Recount Text Writing Skill Of Class X MAS PP. Raudlatul Hasanah - Rera Rizki Agustina, Yulia Sari Harahap (Ability: Journal of Education and Social Analysis, 2022)
This study attempts to find out about the effect of diary on students’ writing skill in recount text. The objective of the study is to discover whether the effect of writing diary technique could significantly increase students’ interest in developing their writing skill especially in recount text. And to find out the ability of students before and after using this technique. This study was conducted by applying experimental design. Two classes where involved in this research, experimental class and control class. The experimental class consists of the students who received treatment. The subject of this study of tenth grade students of Raudlatul Hasanah which consisted of 30 students each class. The test is based on students’ writing on their daily diary with the component of writing : the content, organization, vocabulary which was analyzed by using T-test formula. It was shown from of the score of the students with the calculation of t-test (4,41) with degree of freedom (df) = 58 was higher than ttable (1,67) (p=58) . There is significant effect on students’ scores in each writing test. Therefore, it can be concluded that diary writing affected students’ recount text writing skill.